2010
DOI: 10.1155/2011/571721
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antidiabetic, Antihyperlipidemic, and In Vivo Antioxidant Properties of Sphaeranthus indicus Linn. in Type 1 Diabetic Rats: An Identification of Possible Biomarkers

Abstract: The present investigation was aimed to study the antidiabetic, antihyperlipidemic, and in vivo antioxidant properties of the root of Sphaeranthus indicus Linn. in streptozotocin- (STZ-) induced type 1 diabetic rats. Administration of ethanolic extract of Sphaeranthus indicus root (EESIR) 100 and 200 mg/kg to the STZ-induced diabetic rats showed significant (P < .01) reduction in blood glucose and increase in body weight compared to diabetic control rats. Both the doses of EESIR-treated diabetic rats showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 39 publications
(35 reference statements)
2
36
0
Order By: Relevance
“…Our results revealed that liver and kidney MDA levels significantly increased in rats with experimental diabetes in comparison with the non-diabetic control group. In agreement with our study, Kakkar et al (1997), , Punitha et al (2006), Selvan et al (2008), Chakraborty and Das (2010), Kamel et al (2011), andRamachandran et al (2011) reported that STZ administration increased hepatic and renal MDA levels. The rise in hepatic MDA levels may be due to the high concentration of FFAs in diabetic animals compared with the non-diabetic control group as a consequence of the decrease in plasma insulin levels.…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed that liver and kidney MDA levels significantly increased in rats with experimental diabetes in comparison with the non-diabetic control group. In agreement with our study, Kakkar et al (1997), , Punitha et al (2006), Selvan et al (2008), Chakraborty and Das (2010), Kamel et al (2011), andRamachandran et al (2011) reported that STZ administration increased hepatic and renal MDA levels. The rise in hepatic MDA levels may be due to the high concentration of FFAs in diabetic animals compared with the non-diabetic control group as a consequence of the decrease in plasma insulin levels.…”
Section: Discussionsupporting
confidence: 92%
“…STZ was dissolved in freshly prepared 0.1 M cold citrate buffer (pH 4.5) and administered by intraperitoneal route (60 mg/kg) to the overnight fasted rats [9] . After 6 h of STZ injection, rats were received 5% dextrose solution for the next 24 h to prevent STZ induced fatal hypoglycemia as a result of massive pancreatic insulin release after its administration [10] .…”
Section: Induction Of Experimental Diabetes In Ratsmentioning
confidence: 99%
“…Diabetes was confirmed 72 h after induction by measurement of tail vein blood glucose levels using glucose meter (Glucocard™ 01-mini, Arkray Factory, Inc., Japan) by glucose oxidase-peroxidase method using strips. Diabetic rats were kept 14 days under standard laboratory condition for the stabilization of blood glucose levels [9] . After 14 days induction of diabetes, blood glucose was again determined and animals with a blood glucose level greater than 250 mg/dL were selected for the study.…”
Section: Induction Of Experimental Diabetes In Ratsmentioning
confidence: 99%
“…This possible mechanism was observed in several studies, which reported the hypoglycemic activity of plant extracts that have high content of polyphenolic compounds, such as: Cinnamomum parthenoxylon (Jia et al, 2009), Lactuca indicates (Hou et al, 2007), Dimocarpus longan (Li et al, 2015), Bauhinia monandra (Alade et al, 2012) and Sphaeranthus indicus (Ramachandran et al, 2011).…”
Section: Resultsmentioning
confidence: 81%